2021
DOI: 10.1108/reps-12-2020-0183
|View full text |Cite
|
Sign up to set email alerts
|

Wind energy in the Gulf Cooperation Council region: progress, challenges and strategies for development

Abstract: PurposeUntil recently, the Gulf Cooperation Council (GCC) region, whose members consist of Saudi Arabia, the United Arab Emirates, Kuwait, Qatar, Oman and Bahrain, has not significantly focused on the green transition. Specifically, wind energy development has made minimal progress relative to that of other regions.Design/methodology/approachThe abundance of cheap fossil fuels in the region has not incentivized renewable energy development, and where this has taken place solar technologies are often preferred.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…In response to the economic challenges and threat of scarce oil resources in the current and future times, Momani (2008) stated that the GCC countries have paid more attention to their investors' concerns on investment decisions (Garas & ElMassah, 2018;Issa & Fang, 2019;Platonova, Asutay, Dixon, & Mohammad, 2018). Thus, managers come up with better strategies to increase investment sustainability and meet social aspiration (Alhowaish, 2016;Connelly & Xydis, 2021;Fatima et al, 2022).…”
Section: Earning Management and Sustainable Investment Opportunitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In response to the economic challenges and threat of scarce oil resources in the current and future times, Momani (2008) stated that the GCC countries have paid more attention to their investors' concerns on investment decisions (Garas & ElMassah, 2018;Issa & Fang, 2019;Platonova, Asutay, Dixon, & Mohammad, 2018). Thus, managers come up with better strategies to increase investment sustainability and meet social aspiration (Alhowaish, 2016;Connelly & Xydis, 2021;Fatima et al, 2022).…”
Section: Earning Management and Sustainable Investment Opportunitiesmentioning
confidence: 99%
“…Therefore, governments in those countries encourage and support companies to achieve sustainable investment opportunities with higher growth opportunities and community aspiration. (Alhowaish, 2016;Connelly & Xydis, 2021;Fatima, Mentel, Doğan, Hashim, & Shahzad, 2022). Gulf Cooperation Council (GCC) countries hold an essential part of the world's (Hasan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, high up-front costs of renewable energy technologies and long payback periods have been barriers that disadvantage the competitiveness of renewable energy technologies with conventional energy sources [11,15,19,21]. This has been highly advantaged by the current sector's law that specifies technology, economic, and technical conditions in favor of oil and gas-based technologies.…”
Section: Technical Barriers: Unfamiliarity With New Technical Challen...mentioning
confidence: 99%
“…Furthermore, market distortions, especially subsidized fuel and electricity, have led to low energy prices in the region and were identified as a major challenge that has discouraged the competitiveness of renewables compared to conventional energy sources [14,16]. A recent study identified the design and implementation of financial policies to support renewable energy adoption, which has been a challenge for their large-scale adoption [19,20]. These investigations provide a good explanation of why the share of renewable energy in the GCC has remained low.…”
Section: Introductionmentioning
confidence: 99%
“…UAE is not only investing inside the country, but also in neighboring gulf countries. For example, Masdar a subsidy of Mubadala such as Dhofar wind farm the first utility scale in GCC region with 50 MW in Oman and Dumat Al Jandal with 400 MW This Journal is licensed under a Creative Commons Attribution 4.0 International License capacity in Saudi Arabia are some significant investment projects in addition to its investment in 12 wind farms around the world (Connelly and Xydis, 2021).…”
Section: Introductionmentioning
confidence: 99%